Comparison Of Transfer Accuracy Among Hexed Implant Mounts, Clips Impression Copings, And Open-Tray Impression Copings at Different Implant Angulations: An In Vitro Study - Merna M. Seif; Ahmed A. Abdel Hakim; Hassan M. Abouelkheir; Rana A. Negm (BMC Oral Health)
Abstract Background Accurate impression registration is essential for transferring the three-dimensional (3D) implant position to the definitive cast, ensuring passivity of the final prosthesis. Various impression techniques have been developed to optimize accuracy, particularly for angulated implants. This study aimed to evaluate and compare the accuracy of open-tray impression copings, clips impression copings, and hexed implant mounts in transferring implant positions for both straight and angulated implants. Methods Five implants with different angulations (three at 0°, one at 15°, and one at 25°) were placed in an epoxy resin model, reflecting angulations commonly encountered in clinical practice. Thirty impressions were made using three types of impression copings: open-tray, clips (closed-tray), and hexed implant mounts (closed-tray), with ten impressions per group. Impressions were poured, and CBCT scans of the reference model and casts were obtained. The resulting DICOM files were converted to STL format using reverse engineering software to evaluate implant position accuracy based on shoulder deviation, apical deviation, angular deviation, and vertical shift. A significance level of p < 0.05 was set. One-way ANOVA and post hoc tests were performed; Tukey’s HSD was applied when variance homogeneity was met, while the Games-Howell test was used when this assumption was violated. Results The study revealed that among the three coping types, the hexed implant mount demonstrated significantly higher angular deviation (p < 0.001), apical deviation (p = 0.003), and vertical shift (p < 0.001) for 25° angulated implants compared to the open-tray and clips copings. There were no significant differences between the open-tray and clips groups at this angulation. At 15° angulation, the hexed implant mount showed a significantly greater vertical shift (p = 0.011) compared to the open-tray coping, while no significant difference was observed between the clips and open-tray copings. For straight implants (0° angulation), all three coping types—open-tray, clips, and hexed implant mounts—showed no significant differences in any measured parameter. Conclusions Open-tray and clips impression copings provide reliable implant position transfer for straight and angulated implants up to 25°. The hexed implant mount is accurate up to 15° angulation but shows increased deviations at 25°.